Non-uremic calciphylaxis in a woman without end-stage renal disease. Issue 2 (26th February 2021) - Hodson, Meghan; Kaur, Gurleen; Lin, George; Coates, Andrew
Abstract : A woman in her 60s with a history of lower extremity vascular disease presented with extreme pain and wounds in her legs which had kept her from walking for several weeks. The patient's pain became intolerable throughout her hospital stay despite multiple surgical revascularisations. Biopsy of the patient's calf wounds revealed evidence of calciphylaxis, a diagnosis which corresponds with this patient's extreme pain. Our patient had no history of end-stage renal disease.